Engels revisited : new feminist essays - Sayers, Janet; Evans, Mary; Redclift, Nanneke (London : Tavistock Publications, 1987)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: Engels, Friedrich; feminisme